Number of larval instars of the ant Pachycondyla (=Neoponera) villosa (Formicidae: Ponerinae) determined by the rule of Dyar - Zara, Fernando José [UNESP]; Caetano, Flávio Henrique [UNESP] (My University, 2001)
In this work we present the number of larval instars in the Ponerinae ant Pachycondyla (=Neoponera) villosa. The analysis of maximal head capsule width measurement of 147 larvae was made. Four larval instars were measured: 1st instar the cephalic capsule varied from 0.18mm to 0.22mm; 2nd instar from 0.23mm to 0.27mm; 3rd instar from 0.30mm to 0.33mm and the 4th instar varied from 0.35mm to 0.38mm. The mean growth rate was 1.2375 according to the rule of Dyar. We also reviewed the number of larval instars for 35 ant species.
Keywords: Ants; Dyar's rule; Head capsule; Larval instars; Pachycondyla